Pergeseran Peran Tuan Guru Dalam Kontestasi Politik Lokal Di Nusa Tenggara Barat - Lavica Anky Riswanda (Jurnal Mengkaji Indonesia, 2022)
Abstract: This paper reveals the fact that Tuan Guru in the new order era did what Joel Migdal called a social and political exchange network. Where political support for Golkar was exchanged for interests with expanding influence through da'wah throughout Lombok which was used to reduce the hegemony of Wetu Telu Islam. In the Reformation era, there was a shift in Tuan Guru's role from a political mobilizer to a political actor by filling political positions in both executive and legislative positions. Tuan Guru utilizes the democratic electoral system to expand his social and political influence. In his journey, Tuan Guru did what is called Sidel by maintaining his political dominance through the placement of relatives, and cronies as regional heads and members of the regional legislature in various political positions in NTB. Purpose: This paper wants to discuss the role of Tuan Guru in the local political arena from the New Order era to the Reformation era in NTB. Design/Methodology/Approach: This research is a descriptive qualitative research Originality/Value: Similar research to this study is about the influence of Tuan Guru on political contestation in NTB. It's just that it doesn't discuss the shift in the role of Tuan Guru in political contestation, so this paper presents a novelty on the role of Tuan Guru in political contestation in NTB